Cardiopulmonary exercise testing following bilateral thoracoscopic sympathicolysis in patients with essential hyperhidrosis. Issue 10 (October 1995) - Noppen, M; Herregodts, P; Dendale, P; D'Haens, J; Vincken, W
Abstract : BACKGROUND–Essential hyperhidrosis is characterised by an overactivity of the sympathetic fibres passing through the upper dorsal sympathetic ganglia D2-D3. Anatomical interruption at the D2-D3 level is a highly effective treatment for essential hyperhidrosis but also causes (partial) cardiac denervation and, after surgical sympathicolysis, important impairment of cardiopulmonary exercise function has been observed. The purpose of this study was to compare the results of cardiopulmonary exercise testing between patients with essential hyperhidrosis and a normal control population, and to examine the effects of thoracoscopic D2-D3 sympathicolysis on cardiopulmonary exercise capacity in patients with essential hyperhidrosis. METHODS–maximal, symptom limited incremental exercise tests were performed in 26 patients with severe essential hyperhidrosis one week before and one month after D2-D3 thoracoscopic sympathicolysis, and in 14 age and sex matched healthy volunteers. D2-D3 thoracoscopic sympathicolysis was performed using a simplified one stage bilateral procedure. RESULTS–Palmar hyperhidrosis was relieved in every patient, confirming the D2-D3 denervation. A higher peak heart rate (7%) was seen in the patient group than in the normal subjects, but ll other cardiovascular, metabolic, and respiratory parameters were similar. After D2-D3 thoracoscopic sympathicolysis, heart rate at rest (13%) and at peak exercise (7%) were reduced, together with an increase in oxygen pulse. All other parameters remained unchanged. CONCLUSIONS–Sympathetic overactivity relevant to cardiovascular function in essential hyperhidrosis is evident only during sympathetic stimulation. D2-D3 thoracoscopic sympathicolysis causes a small and asymptomatic reduction in maximal and resting heart rate and is not associated with a decrease in exercise capacity, in contrast with the detrimental effects on exercise capacity of open surgical sympathectomy.